Pengembangan Sistem Informasi Kesehatan Primer untuk Mendukung Penerapan Model Organisasi dan Manajemen Kesehatan Primer ANDAL pada Poliklinik Pabrik Gula Kebon Agung - Fathir Izzuddin Qisthi; Ismiarta Aknuranda; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
"ANDAL", The Primary Healthcare Organization and Management Model is a model that contains the primary healthcare service guidelines. In the implementation of the model, it needs technology support in the management of primary health information so that healthcare providers can provide higher quality primary healthcare services. This research was conducted to develop a health information system, started by performing requirements analysis with the results of the identification of system capabilities being visualized into the use case diagram. Furthermore, the information system modeling was performed to produce an object model and object interaction model in UML notation, and database design. Then, the implementation was performed and produced a web-based Primary Healthcare Information System that provides primary healthcare information management function and the function of calculating the level of risk of the disease and the level of stress that can be used to help healthcare providers determine healthcare intervention to be given to the patient. Furthermore, a system testing showed that the developed system can be run in accordance with the identified requirements.